2016
DOI: 10.3390/molecules22010030
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Cell Death and Its Epigenetic Mechanisms in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease involving multiple organs and tissues, which is characterized by the presence of excessive anti-nuclear autoantibodies. The pathogenesis of SLE has been intensively studied but remains far from clear. Increasing evidence has shown that the genetic susceptibilities and environmental factors-induced abnormalities in immune cells, dysregulation of apoptosis, and defects in the clearance of apoptotic materials contribute to the development of SLE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 94 publications
0
26
0
Order By: Relevance
“…Accumulated ACs are a contributing factor for the exposure of autoantigens to the immune system that eventually leads to autoimmunity like SLE [1,18]. Herein we showed that ACs could be engulfed by UC MSCs and these MSCs exhibited enhanced immunosuppressive function through the activation release of PGE2, which involved NF-κB signalling pathway.…”
Section: Discussionmentioning
confidence: 85%
“…Accumulated ACs are a contributing factor for the exposure of autoantigens to the immune system that eventually leads to autoimmunity like SLE [1,18]. Herein we showed that ACs could be engulfed by UC MSCs and these MSCs exhibited enhanced immunosuppressive function through the activation release of PGE2, which involved NF-κB signalling pathway.…”
Section: Discussionmentioning
confidence: 85%
“…This process plays an integral role in biological functions as diverse as tissue turnover [3], adaptive immunity [4], angiogenesis [5], and normal wound healing [6,7]. Subtle alterations in apoptosis susceptibility of a particular cell population can be a necessary part of homeostasis or can contribute to disease pathogenesis [812]. For these reasons, apoptosis is a far-reaching and popular subject of interest in many biological research laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Although microparticles have been described in systemic lupus erythematous [17,18], they appear to be unrelated to the microcomplexes described herein because they are too large (0.1-1.0 μm) to pass through 10 kDa cut-off ultrafilters.…”
Section: Discussionmentioning
confidence: 81%